Manual de funciones y su incidencia en los diferentes departamentos del Gobierno Autónomo Descentralizado Municipal del Cantón Patate, Provincia de Tungurahua período 2011 - 2012. - Ruiz Naranjo, Flor Paulina (2013)
The Patate Canton Municipal GAD, is located in the "strip Ambato and Juan Montalvo" south eastern province of Tungurahua. The feasibility analysis of the system on the administrative management of the Municipal GAD Patate, considering much today with all the technological advances. The study has the support of the mayor, in order to correctly apply the functions performed responsibly, efficiently and effectively. Such information this Constitution, Public Service Law, Rules of the LOSEP, COOTAD, Code of Public Finance, Internal Control Regulations of the Comptroller, texts, laws, interviews, surveys, brochures, internet, scientific articles, texts, virtual libraries, research. The results of the surveys showed that staff know their roles in the Municipal Government of Autonomous Decentralized Patate sang also indicated that this weakness could be the cause of problems in operating order also affects the development of activities different areas, since no area managers maintain an efficient work coordination. The results of the interviews indicated that the GAD office based on state laws and regulations, but clearly has not done a proper performance evaluation, according to the needs of the workplace and the organic structure of the entity. The field study showed that the hypothesis is positive "Functions Manual affects work performance of officials of the various departments of the Canton Municipal GAD Patate Tungurahua province during 2011-2012"